Rainfall fluctuations in India and Sri Lanka And large-scale rainfall anomalies - FLEER, HERIBERT; SCHWEITZER, BEATE; RAATZ, WOLFGANG (MAUSAM, 1984)
Statistical methods were used to investigate the homogeneity, temporal trends, and spatial and temporal distribution of fluctuations in rainfall series for stations in India and Sri Lanka. The investigations also looked at teleconnections between Indian rainfall and rainfall in the equatorial Pacific dry zone. It appears to be no uniform trend in India over the last 100 years, but significant long-period fluctuations are evident at certain Indian stations. These appears to be a linkage between the recurrent Indian droughts and the El nino phenomena along the west coast of South America.